THE CHANGING INTENTION TO PRACTICE HEALTHY EATING BEHAVIOUR AMONG LATE ADOLESCENTS DURING COVID-19 (Journal of Business Management and Accounting, 2021)
The Covid-19 pandemic has generated intention among late adolescents to practice healthy eating behaviour. Although it is not new, there is limited research on this topic. To date, the pandemic has changed the behaviour of late adolescents to practice healthy eating behaviour. As such, it has tremendously grabbed the attention of scholars amid the Covid-19 pandemic. In addition, the development process from adolescence to late adolescence stage has become a serious healthrelated issue worldwide. However, most research are focused on adolescents instead of late adolescents. Late adolescence is a special group of the population who has specific health concerns. To discover more about healthy eating behaviours among late adolescence aged between 18-24 years in Malaysia, this study aims to examine the 62 Journal of Business Management and Accounting, Vol. 11, Number 2 (July) 2021, pp: 61–72 determinants that contribute to the eating behaviour in this population. Based on past and current literature reviews, a proposed research framework was developed, along with some untested assumptions which were formulated for the research purpose.